(untitled) (Indian Journal of Public Health Research & Development, 2022)
In-hospital cardiac arrest is preceded by the deterioration of a patient’s physiological parameters and vital signs. Identifying and appropriately managing these vital parameters timely can be helpful in reducing in-hospital cardiac arrest and death. Therefore, the initiation of rapid response at the first sign of clinical deterioration has helped the medical team for assessing the risk at early stage and effectively manage their care. The objectives of the study illustrated that to assess the effect of an RRS in reducing the code blues in non-ICU in selected hospitals Pune City, to determine the effects of RRS in reducing the incidence of unexpected deaths, cardiac arrest and CPR. Systematic observation of all the non-critical care patients been included in the study. All the data been collected from the health records. The analysis of the study shows that 92% possible codes prevented after implementation of MEWS & RRS which also increases the total number of elective transferring of patient to the Intensive care unit.